Statistical significance and clinical relevance in dentistry - Arriola-Guillén, Luis Ernesto (2022)
Dentists face very important clinical decisions in their daily dental practice, which is why they permanently require scientific support to support them, clearly for the benefit of patients. However, sometimes, in the scientific literature, results with statistically significant differences are found, which causes clinicians to have to opt for a particular treatment alternative; but it turns out that it could be a significant difference that is not clinically relevant, and this raises the question of what decision to make.